Pengaruh Promosi Video Pendek di Instagram Buddy Pool terhadap FOMO Billiard Generasi Z - Edward, Joshua; Candraningrum, Diah Ayu (Kiwari, 2025)
This study examines the influence of short videos in Buddy Pool’s Instagram account on the behavior of Fear of Missing Out (FOMO) within the billiard trend among Generation Z in West Jakarta. Using a quantitative approach and survey method, the data were collected from 100 respondents aged 18–25 through an online questionnaire. The findings reveal that short videos on Instagram significantly affect FOMO behavior, with creative content such as tutorials, facility promotions, and community activities successfully capturing attention and increasing audience participation. The impact of short videos on FOMO was measured at 12.6%, while other factors accounted for the remainder. These results highlight the importance of social media as an effective promotional device for creating trends, expanding marketing reach, and strengthening connections with young audiences. Penelitian ini menganalisis pengaruh video pendek di Instagram Buddy Pool terhadap fenomena Fear of Missing Out (FOMO) dalam tren biliar dalam kalangan Generasi Z Jakarta Barat. Dengan pendekatan kuantitatif dan metode survei, data dikumpulkan dari 100 responden berusia 18–25 tahun menggunakan kuesioner online. Hasil penelitian menunjukkan bahwa video pendek di Instagram berpengaruh signifikan terhadap perilaku FOMO, dimana konten kreatif seperti tutorial, promosi fasilitas, dan aktivitas komunitas berhasil menarik perhatian dan meningkatkan partisipasi audiens. Pengaruh video pendek terhadap FOMO tercatat sebesar 12,6%, sementara sisanya dipengaruhi oleh faktor lain. Temuan ini menegaskan pentingnya media sosial sebagai perangkat promosi yang efektif untuk menciptakan tren, memperluas jangkauan pemasaran, dan memperkuat koneksi dengan generasi muda.